Evaluation of Fucokinase in groups of postmenopausal patients due to hormonal, surgical, and genetic disorders - Omar, Duaa H.; Al-Helaly, Luay A. (Edelweiss Applied Science and Technology, 2026)
Fucokinase (FUK) is involved in the process of fucosylation of carbohydrates, which are involved in various biological and pathological processes. FUK, in addition to some hormones, lipid profiles, oxidants and antioxidants, and vitamin D, were measured in serum for 175 women aged 18–40 years. The 80 serum samples were collected from women suffering from menopause within the same age range from Mosul city. The appearance of a decrease in FUK activity in all types of postmenopausal patients is due to hormonal, surgical, and genetic disorders, especially the surgical type, compared to healthy women. There is a state of high oxidative stress in all types of menopause, particularly in genetic disorder cases, characterized by decreased glutathione and increased malondialdehyde and peroxynitrate. Lipid profile levels showed disorder only in hormonal disorder cases. An increase in progesterone and testosterone levels was observed in hormonal and surgical disorder types, while a decrease was noted in genetic disorder cases. Additionally, vitamin D levels decreased in this group. The findings emphasize the importance of monitoring oxidative stress markers in this population.